2022
DOI: 10.46483/deuhfed.946855
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemi Sürecinde Hemşirelik Öğrencilerinin E-Öğrenmeye İlişkin Tutumları ile Öğrenme Algıları Arasındaki İlişkinin İncelenmesi

Abstract: Giriş: COVID-19 pandemi sürecinde bütün eğitim kurumları kapatılarak geleneksel eğitim acil uzaktan eğitim sürecine göre şekillendirilmiş, dersler uzaktan eğitim ile yürütülmüştür. Amaç: Bu çalışma hemşirelik öğrencilerinin e-öğrenmeye yönelik tutumları ile algılanan öğrenme arasındaki ilişkinin incelenmesi amacıyla yapılmıştır. Yöntem: Tanımlayıcı kesitsel nitelikte yürütülen bu çalışmanın örneklemini 2020-2021 eğitim-öğretim döneminde bir üniversitenin hemşirelik bölümünün ikinci, üçüncü ve dördü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…It can be thought that this situation is due to the better infrastructure conditions of urban areas (such as access to the internet, high speed of access to the internet) and easier access to services and opportunities (such as the necessary technological infrastructure and the appropriate environment for e-learning). Similarly, Arslan and Bayram's (2022) study showed a difference between urban districts and villages. This situation was attributed to the fact that the students living in the village had more limited financial means, different home environments, and suffered from the internet infrastructure being less developed.…”
Section: Discussionmentioning
confidence: 88%
“…It can be thought that this situation is due to the better infrastructure conditions of urban areas (such as access to the internet, high speed of access to the internet) and easier access to services and opportunities (such as the necessary technological infrastructure and the appropriate environment for e-learning). Similarly, Arslan and Bayram's (2022) study showed a difference between urban districts and villages. This situation was attributed to the fact that the students living in the village had more limited financial means, different home environments, and suffered from the internet infrastructure being less developed.…”
Section: Discussionmentioning
confidence: 88%
“…With the pandemic, the concept of e-learning has gained importance with the increasing use of online environments in distance or open learning. With the changes in education, e-learning has turned from being an alternative option to a necessary situation during the COVID-19 pandemic process (Arslan & Bayram, 2022). E-learning is the realization of teaching activities in electronic learning environments by interacting with multimedia applications.…”
Section: Introductionmentioning
confidence: 99%
“…Literatür incelendiğinde, e-öğrenmeye yönelik tutumların incelenmesi adına gerçekleştirilen çalışmalara rastlanılmaktadır (Adnan ve Yaman, 2017; Arslan ve Bayram, 2022;Haznedar, 2012;Çakır, 2023;Dinçer, 2022;Garay vd., 2021;Karavida vd., 2021;Kılıç, 2021;Öktem, 2020;Özdemir ve Aydoğan, 2021;Puljak vd., 2020;Şükrü vd., 2021;Tarım ve Uyandıran, 2021;Tarigan, 2021;Yıldız ve Yılmaz, 2022). Bireylerin uyaranlara karşı olan tutumu tespit edebilmek uyarana karşı tepkisinin de ne olduğunu tahmin etmede kolaylık sağlayacaktır (Üstüner, 2006).…”
Section: Introductionunclassified